Proust: Desire and Style, Theory and Criticism. About a Recent Book by Giovanni Botti-roli (ENTHYMEMA, 2024)
Review of Giovanni Bottiroli Marcel Proust. Il romanzo del desiderio (Feltrinelli, 2022).
Keywords: Giovanni Bottiroli; Marcel Proust